The Fresh Eggs Daily cookbook : over 100 fabulous recipes to use eggs in unexpected ways - Steele, Lisa, 1965- (Harper Horizon, 2022)
"Lisa Steele, founder of the popular blog Fresh Eggs Daily, shares the delightful and delicious recipes she uses each day to take advantage of the bounty provided by the feathered friends on her Maine farm"--